Karriervizsgálatok egyetemisták körében - Gergely, Éva (Közép-Európai Közlemények, 2016)
The paper endeavors to give a narrower definition of the concept of ‘career’. The survey to be discussed hereafter examines a sample of 116 full time students of economics, and has career anchor analysis in its focus. The analysis finds that “Security, stability and organizational identification” are judged to be the primary anchors among the members of the bulk sample. This means that the respondents feel ready to identify themselves with the company, and are looking for security to be provided by long term employment, regular earnings and by a steady career advancement. The cluster analysis of the questioner differentiates four groups: Leaders, Specialists, Entrepreneurs, and Employees. I found that the Leaders have high capacities of leadership, creativity, and autonomy. The Specialists show highly developed functional competences in general, and they seem to like challenges. The Entrepreneurs have outstandingly high scores concerning autonomy and entrepreneurial creativity. The members of the cluster of the Employees are characterized by a high expectation of security and stability, and by low levels of managerial competence and entrepreneurial creativity.